Sustainable development and airport surface access: the role of technological innovation and behavioural change. - Ryley, Tim; Elmirghani, Jaafar; Budd, Tom; Miyoshi, Chikage; Mason, Keith J.; Moxon, Richard; Ahmed, Imad; Qazi, Bilal; Zanni, Alberto (MDPI, 2013)
Sustainable development reflects an underlying tension to achieve economic growth whilst addressing environmental challenges, and this is particularly the case for the aviation sector. Although much of the aviation-related focus has fallen on reducing aircraft emissions, airports have also been under increasing pressure to support the vision of a low carbon energy future. One of the main sources of airport-related emissions is passenger journeys to and from airports (the surface access component of air travel), which is the focus of this paper. Two aspects associated with the relationship between sustainable development and airport surface access are considered. Firstly, there is an evaluation of three technological innovation options that will enable sustainable transport solutions for surface access journeys: telepresence systems to reduce drop-off/pick-up trips, techniques to improve public transport and options to encourage the sharing of rides. Secondly, the role of behavioural change for surface access journeys from a theoretical perspective, using empirical data from Manchester airport, is evaluated. Finally, the contribution of technology and behavioural intervention measures to improvements in sustainable development are discussed.